إدارة مخاطر سعر الفائدة والتحوط منها باستخدام العقود الآجلة - عبود ريم محمد (Latakia University Journal - Economic and Legal Sciences Series, 2013)
تتعرض البنوك التجارية في ظل التغيرات المستمرة في البيئة الاقتصادية, إلى العديد من المخاطر التي تؤثر على أنشطتها المختلفة من إقراض, واستثمار, وغيرها, حيث تعتبر مخاطر سعر الفائدة من المخاطر التي تؤثر بشكل مباشر على دخل المصرف, لذلك هدف هذا البحث التعريف بمخاطر سعر الفائدة وأهم مصادرها, والتحوط منها باستخدام العقود الآجلة, للحد من آثارها السلبية على ربحية المصرف, وذلك من خلال قياس هذه المخاطر باستخدام فجوة إعادة التسعير, وأثرها على صافي الفوائد. وأهم ما توصل إليه البحث من نتائج, استخدام المصارف طريقة فجوة الاستحقاق كطريقة أساسية لقياس مخاطر سعر الفائدة , وتفاوت حجم ونوع الفجوة التراكمية في البنوك عينة الدراسة(مصرف سورية والمهجر , المصرف العربي) خلال فترة الدراسة (2006- 2011), وتأثر صافي الفوائد الفعلية بقيمة ونوع الفجوة التراكمية, وباتجاه تغير سعر الفائدة, الذي كان يتجه للانخفاض طيلة مدة الدراسة. وإن استخدام إستراتيجية إتفاقيات الفائدة الآجلة في إدارة مخاطر أسعار الفائدة, قد ساهم في التقليل من هذه المخاطر وحقق التحوط للمصرفين عينة الدراسة. Exposed commercial banks in the light of the constant changes in the economic environment, many of the risks that affect the various activities of lending, investment, etc., where the risk is interest rate risk, which directly affect the income of the bank, so the goal of this research definition of risk interest rate The most important sources, including hedging using futures contracts, to reduce the negative impact on the profitability of the bank, through the measurement of these risks by using the re-pricing gap, and their impact on net interest income. The most important findings of the research results, the use of banks method gap maturity as a way essential to measure the interest rate risk, and the varying size and type of the gap accumulated in the banks the study sample (Bank of Syria and Overseas, Arab Bank) during the study period (2006 - 2011), and was influenced by the net effective interest the value and type of the cumulative gap, and change the direction of the interest rate, which was heading for the low for the duration of the study. The use of interest rate futures agreements strategy in the management of interest rate risk, has contributed to the reduction of these risks and hedge achieved for the sample banks....